2016
DOI: 10.1007/s00595-016-1314-8
|View full text |Cite
|
Sign up to set email alerts
|

Sublobar resection versus lobectomy for stage I non-small cell lung cancer: an appropriate choice in elderly patients?

Abstract: High-risk elderly patients may benefit from sublobar resection, which provides an equivalent long-term survival compared to lobectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 27 publications
1
55
2
1
Order By: Relevance
“…Tsutani et al 3 found no statistically significant difference in overall survival (OS) or recurrence-free survival between patients treated by segmentectomy versus wedge resection for ground glass opacity (GGO)-dominant clinical stage Ia NSCLC. Similar results have been reported by Fiorelli et al, Hamatake et al, and Kent et al [4][5][6] Hou et al 7 conducted a meta-analysis of nine studies and found no significant difference in disease-free survival (DFS) of patients with stage I NSCLC receiving segmentectomy versus wedge resection. Some previous metaanalyses that have compared the clinical outcomes of lobectomy, segmentectomy, and wedge resection in patients with stage I NSCLC categorized segmentectomy and wedge resection together as "sublobar resection."…”
Section: Introductionsupporting
confidence: 80%
“…Tsutani et al 3 found no statistically significant difference in overall survival (OS) or recurrence-free survival between patients treated by segmentectomy versus wedge resection for ground glass opacity (GGO)-dominant clinical stage Ia NSCLC. Similar results have been reported by Fiorelli et al, Hamatake et al, and Kent et al [4][5][6] Hou et al 7 conducted a meta-analysis of nine studies and found no significant difference in disease-free survival (DFS) of patients with stage I NSCLC receiving segmentectomy versus wedge resection. Some previous metaanalyses that have compared the clinical outcomes of lobectomy, segmentectomy, and wedge resection in patients with stage I NSCLC categorized segmentectomy and wedge resection together as "sublobar resection."…”
Section: Introductionsupporting
confidence: 80%
“…As lobectomy with systematic lymph node dissection is the current strategy for management of NSCLC in patients able to tolerate it, in theory T‐ALI should be treated as two primary tumors in different lobes. Thus, pneumonectomy, or at least bilobectomy (right lung) is more reasonable than lobectomy associated with sublobar resection in order to obtain a complete tumor resection and, thus reduce the risk of loco‐regional recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…Despite high‐quality evidence from multi‐institutional randomized controlled trials evaluating the efficacy of lobectomy versus sublobar resection in NSCLC (Cancer and Leukemia Group B 140503 trial, Japan Clinical Oncology Group 0802, and West Japan Oncology Group 4607L trial), an increasing number of retrospective reviews have demonstrated that sublobar resection is an acceptable alternative to lobectomy in patients with early‐stage NSCLC . Several recent studies have identified that sublobar resection is an effective equivalent to lobectomy for selected patients with stage IA NSCLC . Moreover, a recent study using SEER data demonstrated that sublobar resection is not inferior to lobectomy, even in patients aged ≤ 35 years with stage IA NSCLC .…”
Section: Discussionmentioning
confidence: 99%